The impact of pharmacists’ interventions within the Closed Loop Medication Management process on medication safety: An analysis in a German university hospital - Berger, Vivien; Sommer, Christian; Boje, Peggy; Hollmann, Josef; Hummelt, Julia; König, Christina; Lezius, Susanne; Linde, Annika van der; Marhenke, Corinna; Melzer, Simone; Michalowski, Nina; Baehr, Michael; et al. (Frontiers in Pharmacology, 2022)
Background Single elements of the Closed Loop Medication Management process (CLMM), including electronic prescribing, involvement of clinical pharmacists (CPs), patient individual logistics and digital administration/documentation, have shown to improve medication safety and patient health outcomes. The impact of the complete CLMM on patient safety, as reflected in pharmacists’ interventions (PIs), is largely unknown. Aim To evaluate the extent and characterization of routine PIs performed by hospital-wide CPs at a university hospital with an implemented CLMM. Methods This single-center study included all interventions documented by CPs on five self-chosen working days within one month using the validated online-database DokuPIK (Documentation of Pharmacists’ Interventions in the Hospital). Based on different workflows, two groups of CPs were compared. One group operated as part of the CLMM, the “Closed Loop Clinical Pharmacists” (CL CPs), while the other group worked less dependent of the CLMM, the “Process Detached Clinical Pharmacists” (PD-CPs). The professional experience and the number of medication reviews were entered in an online survey. Combined pseudonymized datasets were analyzed descriptively after anonymization. Results A total of 1,329 PIs were documented by nine CPs. Overall CPs intervened in every fifth medication review. The acceptance rate of PIs was 91.9%. Most common reasons were the categories “drugs” (e.g. indication, choice of formulation/drug and documentation/transcription) with 42.7%, followed by “dose” with 29.6%. One quarter of PIs referred to the therapeutic subgroup “J01 antibacterials for systemic use”. Of the 1,329 underlying PIs, 1,295 were classified as medication errors (MEs) and their vast majority (81.5%) was rated as “error, no harm” (NCC MERP categories B D). Among PIs performed by CL-CPs (n=1,125), the highest proportion of errors was categorized as B (56.5%), while in the group of PIs from PD-CPs (n=170) errors categorized as C (68.2%) dominated (p<0.001). Conclusion Our study shows that a structured CLMM enables CPs to perform a high number of medication reviews while detecting and solving MEs at an early stage before they can cause harm to the patient. Based on key quality indicators for medication safety, the complete CLMM provides a suitable framework for the efficient medication management of inpatients.